Valorization of Albedo Orange Peel Waste to Develop Electrode Materials in Supercapacitors for the Electric Industry - Gladis G. Suárez; José A. Ramírez; Juan F. Castañón; Jorge A. Galavíz; Perla C. Meléndez (Journal of Chemistry)
This work proposes the use of albedo of orange peel in generation of carbon for applications in supercapacitors. For this, a comparison of compositional and electrochemical properties present in the carbons obtained of albedo, flavedo, and the complete orange peel was carried out. The morphology and composition of carbons obtained were analyzed by Field Emission Scanning Electron Microscopy (FESEM), Energy Dispersive X-ray (EDX), X-Ray Diffraction (XRD), and Fourier-transform infrared spectroscopy (FT-IR). The synthetized carbons were not subjected to the activation process by chemical compounds to relate only the properties of orange peel parts with their electrochemical behaviour. All samples were tested by cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). The carbon obtained of albedo presented a superior specific capacitance (210 F/g) of the rest samples. The value of albedo-based carbon capacitance is comparable with works presented in the literature that used a whole orange peel with chemical activators. In this way, it is possible to obtain large capacitances using only a part of orange peel (albedo). Thus, the importance of this study is that the albedo can be proposed as a material applied to electrodes for supercapacitors while the flavedo can be used in food industry or for oil extraction.